Papuloerythroderma with Associated Non Hodgkin’s Lymphoma : A Rare Entity - Jagati, Ashish; Agarwal, Pooja; Neazee, Sabha; Shah, Sanjeev Y (Nepal Journal of Dermatology, Venereology & Leprology, 2020)
Papuloerythroderma of Ofuji was first described by Ofuji in 1984. This rare entity is characterized by presence of polygonal, erythematous to brown papules, covering the entire body surface, with a characteristic sparing of body folds (deck chair sign). On hematological investigations, there is characteristic eosinophilia with lymphopenia. It may or may not be associated with underlying malignancies. We report a case of a 81 year male patient where a diagnosis of Papuloerythrodrma secondary to non-Hodgkin`s lymphoma was made based on the criteria laid by Torchia et Al. Our patient satisfied 4 out of 5 major criteria and all 5 of the minor criteria. This case is reported because of its rarity and characteristic clinical presentation.